PRODUKTIVITAS TENAGA KERJA PADA PROYEK PEMELIHARAAN JALAN TALAGA – SANGIANG KAB. MAJALENGKA - Alya, Rio; Heryadiana, Asep Dian (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Road maintenance is an effort to improve road conditions that are functionally feasible and structurally feasible, so the handling of roads must be in accordance with the type of damage experienced by the road. Inappropriate handling will only throw away the budget spent because its function will not be optimal and will definitely break again quickly.A road requires maintenance and maintenance on road construction and parts of the road construction. With road maintenance, it can maintain the condition of the road when the road is completed until the planned age is reached on the road.Damage to the road will cause a lot of losses that can be felt by users directly, because it will certainly hamper the speed and comfort of road users and cause many victims due to road damage that is not immediately handled by the agency that handles it. Basically planning the life of the road pavement is adjusted to the conditions and needs of the existing traffic, generally designed within a time limit of 10-20 years, which means that the road is expected not to suffer damage in the first 5 years. However, if in reality the road is damaged before the first 5 years, then it is certain that the road will experience major problems in the future (Hardiyatmo, 2007).In order to maintain road conditions at a proper performance in serving various modes of transportation, it is necessary to evaluate the road surface to find out whether the road is still in good condition or there is a need for an improvement program for routine maintenance or periodic maintenance. The form of road maintenance depends on the results of the damage condition assessment.road surface that has been determined visually, while several methods that are often used are the Bina Marga method (1990) and the PCI (pavement condition index) method (Hardiyatmo, 2007).